2002
DOI: 10.1016/s0375-9474(02)01126-0
|View full text |Cite
|
Sign up to set email alerts
|

Density dependence of the s-wave repulsion in pionic atoms

Abstract: Several mechanisms of density dependence of the s-wave repulsion in pionic atoms, beyond the conventional model, are tested by parameter fits to a large (106 points) set of data from $^{16}$O to $^{238}$U, including `deeply bound' states in $^{205}$Pb. Special attention is paid to the proper choice of nuclear density distributions. A density-dependent isovector scattering amplitude suggested recently by Weise to result from a density dependence of the pion decay constant is introduced and found to account for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…The combined isoscalar parameter, b 0 + 0.215 ReB 0 = −0.0274 ± 0.0002, is in good agreement with that obtained in the analysis of the 205 Pb [28]. The imaginary part, ImB 0 = 0.0472 ± 0.0013, is consistent with the global-fit value of 0.055 ± 0.003 by Batty et al [26] and Friedman [29,30], considering that they included the angle-transformation (AT) term, which causes an appreciable decrease in the width [27]. In fact, the best-fit value in our analysis with the AT term included is: ImB 0 = 0.058 ± 0.003.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The combined isoscalar parameter, b 0 + 0.215 ReB 0 = −0.0274 ± 0.0002, is in good agreement with that obtained in the analysis of the 205 Pb [28]. The imaginary part, ImB 0 = 0.0472 ± 0.0013, is consistent with the global-fit value of 0.055 ± 0.003 by Batty et al [26] and Friedman [29,30], considering that they included the angle-transformation (AT) term, which causes an appreciable decrease in the width [27]. In fact, the best-fit value in our analysis with the AT term included is: ImB 0 = 0.058 ± 0.003.…”
supporting
confidence: 88%
“…In recent papers we showed that the density-dependent parameter b * 1 (ρ) can be well represented by a constant parameter b 1 [27], and developed a method to deduce the b 1 parameter [28]. The data of the 1s π − state in 205 Pb [20], π [30], although some ambiguity arising from the p-wave part remains. In order to determine b 1 more reliably and accurately, it is essential to perform high-precision spectroscopy on deeply bound 1s π − states in heavy nuclei.…”
mentioning
confidence: 99%
“…This model which was shown [14,15] to explain the anomaly in pionic atoms, is denoted here by W. An alternative approach which was also shown to explain the anomaly in pionic atoms [21] is to replace E by E − V c by imposing the minimal substitution requirement [22], which is effective through the energy dependence of the isoscalar parameter b 0 . This model is denoted here by E. Finally, applying both mechanisms we have the EW model.…”
Section: Discussionmentioning
confidence: 99%
“…Large scale fits to pionic atom data encompassing the whole of the periodic table showed [14,15] that indeed the density-dependence of the pion decay constant [9] which causes the isosvector scattering amplitude to become density dependent, is capable of removing the anomaly. Similar conclusions were also presented [16,4,17,5] on the basis of very restricted data sets, consisting mainly of the recently observed 'deeply bound' states of pionic atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Smaller values of r n − r p were also used in Ref. [4]. In the present work we vary, among other things, the values of r n −r p and we therefore look for a simple parameterization that will be easy to relate to the RMF results.…”
Section: Nuclear Density Distributionsmentioning
confidence: 99%